Vocabulary learning through viewing video: the effect of two enhancement techniques. Issue 1 (2nd January 2018) - Montero Perez, Maribel; Peters, Elke; Desmet, Piet
ABSTRACT: While most studies on L2 vocabulary learning through input have addressed learners' vocabulary uptake from written text, this study focuses on audio-visual input. In particular, we investigate the effects of enhancing video by (1) adding different types of L2 subtitling (i.e. no captioning, full captioning, keyword captioning, and glossed keyword captioning which provides access to meaning) and (2) informing vs. not informing students that viewing would be followed immediately by a test of vocabulary from the video (Test Announcement). The study adopted a 2 (+/- Test Announcement) x 4 (Type of Captioning) between-subject design, resulting in 8 experimental groups. 227 Dutch-speaking university students watched three French (= L2) videos in one of eight conditions. Results revealed that students in the glossed keyword captions group (with access to meaning) scored best on the form recognition and meaning recall tests. Analyses of the look-up behaviour of students in the glossed keyword captioning group revealed that looking up a given word was positively related to the learning of that word. Test Announcement did not affect word learning or look-up behaviour. Participants' vocabulary size was directly related to their learning gains as well as to their look-up behaviour in the glossed keyword condition.